Ultrathin monolithic zirconia veneers: Reality or future? report of a clinical case and one-year follow-up - Souza, R.; Barbosa, F.; Araújo, G.; Miyashita, E.; Bottino, M. A. [UNESP]; Melo, R. [UNESP]; Zhang, Y. (Operative Dentistry, 2018)
Yttria-stabilized polycrystalline zirconia ceramics have greatly advanced over the past few years. High-translucent zirconia is a newly introduced ceramic that affords high strength and esthetics and that has significantly increased the clinical indications of monolithic zirconia restorations. Thus, the purpose of this case report was to evaluate the performance of ultrathin monolithic zirconia veneers adhesively luted to enamel surfaces after minimally invasive preparations; in addition, we aimed at presenting a clinical protocol for zirconia surface treatment in order to promote bonding effectiveness to resin cement. This type of restoration presented very acceptable esthetic results and decreased the risk of fracturing the veneer during try-in and clinical use. The results were still satisfactory after one-year follow-up. However, randomized, prospective, controlled clinical trials are required to determine the long-term clinical durability of this treatment.